2019
DOI: 10.1001/jamainternmed.2019.3505
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Behaviorally Designed Gamification Interventions With Social Incentives for Increasing Physical Activity Among Overweight and Obese Adults Across the United States

Abstract: the use of game design elements in nongame contexts, is increasingly being used in workplace wellness programs and digital health applications. However, the best way to design social incentives in gamification interventions has not been well examined. OBJECTIVE To assess the effectiveness of support, collaboration, and competition within a behaviorally designed gamification intervention to increase physical activity among overweight and obese adults. DESIGN, SETTING, AND PARTICIPANTS This 36-week randomized cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
179
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 117 publications
(216 citation statements)
references
References 37 publications
11
179
0
2
Order By: Relevance
“…The four interventions that encouraged competition all effectively increased physical activity in presence of the intervention. For two of the interventions, effects were also measured after removal of the intervention [114,115]; these effects were significant in one study [115]. Finally, the three studies that provided information about physical activity performances of others all reported a significant effect on physical activity during the intervention.…”
Section: Social Influence (Social Environment)mentioning
confidence: 99%
See 4 more Smart Citations
“…The four interventions that encouraged competition all effectively increased physical activity in presence of the intervention. For two of the interventions, effects were also measured after removal of the intervention [114,115]; these effects were significant in one study [115]. Finally, the three studies that provided information about physical activity performances of others all reported a significant effect on physical activity during the intervention.…”
Section: Social Influence (Social Environment)mentioning
confidence: 99%
“…A total of 23 studies were conducted in a laboratory setting (85-87, 89-103, 105-107) 1 . The remaining studies implemented an intervention through a mobile phone application or website (n = 8) [38,47,113,[115][116][117][118]120], mobile text messages (n = 2) [51,89] or e-mail (n = 2) [40,119].…”
Section: Design and Settingmentioning
confidence: 99%
See 3 more Smart Citations